(untitled) (Balneo and PRM Research Journal, 2021)
Introduction. SARS CoV-2 caused the third global pandemic and by applying quarantine / isolation / lockdown, the movement was restricted, the physical contact between people was reduced, the physical activity was low, but the activities using electronic devices at home were frequent. The aim of the study was to assess the physical and emotional health in relation to the physical activities done during quarantine/ isolation during the pandemic. Material and method. The study was cross-sectional and consisted of completing an online questionnaire. It was conducted in a period of 6 months and it included 334 students. In order to point out the symptoms caused by quarantine / isolation/ lockdown, we considered it useful for students to participate by completing an online questionnaire about physical activities, physical health and emotional state, related to the implications of participating in online courses. Results. The questions in this questionnaire were grouped on the following aspects: physical activity, physical health, emotional state, all in the context of the pandemic period, including the period in which the academic activity was online. Thus, in the first year, there is a positive correlation between physical condition, physical activity, emotional signs and cognitive ones. In the second year, the positive correlation is present between the physical and the affective signs, whereas the negative correlation is between the affective signs, the cognitive ones and the physical activity. In the third year, the positive correlation is obvious between the affective signs, the cognitive ones and the physical activity, whereas the negative one between the physical and cognitive signs, as well as between the physical activity and the cognitive and physical signs. Discussions. There is a link between emotional and cognitive symptoms and physical health. Fear, anxiety, behavioral disorders, and limited physical activity among students during this period can be a public health issue. Conclusions. The COVID-19 pandemic affected the physical and mental state, with a greater resonance for youth, especially pupils and students. Many of them had emotional, behavioral, physical and cognitive symptoms. These symptoms are found to a greater extent in students in the final years, due to the social impact, social and professional integration.